The Importance of Policy Orientation and Environment on Physical Activity Participation - A Comparative Analysis between Eastern Germany, Western Germany and Finland. - Stahl, Timo; Rütten, Alfred; Nutbeam, Don; Kannas, Lasse (Health promotion international, 2002)
Environmental and policy interventions are seen as boosting physical activity because they are designed to influence large groups. However, they have not been much researched and the evidence on their role is still quite limited. The purpose of this study was to investigate differences in and relationships between policy orientation, the objective and perceived physical environment, and physical activity between Finland, Eastern Germany and Western Germany. The data are taken from a public telephone survey carried out as part of the international MAREPS project (Methodology for the Analysis of Rationality and Effectiveness of Prevention and Health Promotion Strategies; Eastern Germany, n = 913; Western Germany, n = 489; Finland, n = 400), statistics of sports facilities and policy documents. Results from the survey showed that Finns are more active than Germans and that they differ in their way of practising physical activity from Germans. Finns were more satisfied with their opportunities for physical activity and were better informed about physical programmes and measures. Finland also has the best opportunities in indoor sports facilities and outdoor sports grounds per number of inhabitants (excluding indoor swimming pools). Analysis of policy orientations showed that Finland had the most extensive 'Sport for All' policy, although West Germany's policy orientation did not differ that much from Finland's. East Germany's policy orientation was characterized by competitive sports. A policy orientation that places emphasis on the physical activity of the whole population seems to be related to better opportunities and a better infrastructure for sports and physical activity. This study suggests that there is a relationship between policy orientation, physical environment and physical activity participation.
UnivIS-Import:2015-03-09:Pub.2002.phil.dps.iss.lsw.theimp
Keywords: Environment; Physical activity; Policy; Sports facilities